Pro-inflammatory markers as predictors of arterial thrombosis in aged patients with peripheral arterial disease post revascularization - Rodriguez Alvarez, Adriana A.; Cieri, Isabella F.; Boya, Mounika Naidu; Patel, Shiv; Agrawal, Aniket; Ferreira, Sasha P. Suarez; Alli, Christianah; Sharma, Shruti; Dua, Anahita (Frontiers in Medicine, 2025)
IntroductionInflammation occurs in the initial stage of arterial atherosclerosis and serves as the first step in thrombus generation, with elevated inflammatory markers predicting myocardial infarction in coronary artery disease patients. Inflammation is known to alter the course of multiple diseases and can thus, also impact recovery post-treatment and surgical outcomes. Yet, there is a paucity of data regarding the relationship between inflammatory biomarkers and arterial thrombotic potential in peripheral artery disease (PAD) patients post-revascularization. Our pilot study attempts to fill this gap by evaluating if the expression of inflammatory biomarkers in PAD patients correlates with the incidence of thrombotic events post-revascularization.MethodsPlasma samples were prospectively collected from PAD patients who underwent revascularization from 2021 to 2023 at monthly time points for 6 months from the procedure. Patients were followed for a total of 6 months post-procedure and those who experienced thrombotic events were identified. Nine patients with thrombotic events and 16 with non-thrombotic events along with 5 healthy volunteers were analyzed. Plasma samples were analyzed for the following pro-inflammatory markers: IL-1β (Interleukin-1 beta), IL-6, and TNF-α (Tumor Necrosis Factor - alpha), GM-CSF (Granulocyte-Macrophage Colony-Stimulating Factor), IFNγ (Interferon-gamma), IL-8, MCP-1 (Monocyte Chemoattractant Protein-1). The Kruskal-Wallis test was performed to compare bio-inflammatory marker levels between groups.ResultsA total of 303 patients were enrolled, of which 59 had thrombotic events. There were no differences between medications or disease burden between groups. Levels of circulating IL-6 and TNF- α were significantly higher in the thrombosis cohort compared to the non-thrombosis cohort (55 vs. 38, p < 0.02) and (159 vs. 110, p < 0.02) respectively. Although there was a trend toward significance for IL-1β between the thrombotic cohort and non-thrombotic cohort, it did not reach statistical significance (18 vs. 11.5, p = NS). There was no difference observed in aspirin’s ability to dampen the inflammatory response between the two groups as all patients were on aspirin between the groups evaluated.ConclusionPro-inflammatory markers IL-6 and TNF-α are significantly increased in patients, 1 month prior to an arterial thrombotic event, as compared to patients without thrombotic events. These biomarkers could predict impending thrombosis in patients with PAD post-revascularization.